Frozen embryo transfer: Endometrial preparation by letrozole versus hormone replacement cycle: A randomized clinical trial - Alamtaj Samsami; Leila Ghasmpour; Sara Davoodi; Shaghayegh Moradi Alamdarloo; Jamshid Rahmati; Ali Karimian; Hamide Homayoon (Shahid Sadoughi University of Medical Sciences, 2019)
Background The endometrial preparation with stimulating natural cycles for frozen embryo transfer (FET) have benefits like lower cost and ease of use. Objective Comparing the clinical outcome of letrozole versus hormone replacement (HR) for endometrial preparation in women with normal menstrual cycles for FET in artificial reproduction techniques. Materials and Methods A total of 167 participants who had frozen embryos and regular ovulatory cycles were randomly divided into two groups for endometrial preparation. One group (82 women) was stimulated with letrozole 5mg/day and the other group (85 women) was hormonally stimulated by oral estradiol valerate (2 mg three times a day). All participants were followed serially by ultrasonography. Any patient who did not reach optimal endometrial thickness was excluded from the study. Implantation, biochemical and clinical pregnancy and abortion rate were reported. Results There was no significant difference in the mean age, duration, and primary or secondary infertility, cause of the infertility, number, and quality of transferred embryos between the groups. The mean estradiol level on the day of transfer was 643 ± 217 in the HR group and 547 ± 212 in the letrozole group (P = 0.01), which was significantly different. The clinical pregnancy rate was 38.7 in the letrozole group, higher than the HR group (25.3) but not significantly different (P = 0.06). Conclusion For endometrial preparation in women with a normal cycle, letrozole yields higher pregnancy rate although it is not significant; due to its cost, ease in use, and lower side effects, letrozole is a good choice.